Vba4p, a vacuolar membrane protein, is involved in the drug resistance and vacuolar morphology of Saccharomyces cerevisiae. Issue 2 (1st February 2016) - Kawano-Kawada, Miyuki; Pongcharoen, Pongsanat; Kawahara, Rieko; Yasuda, Mayu; Yamasaki, Takashi; Akiyama, Koichi; Sekito, Takayuki; Kakinuma, Yoshimi
Abstract: In the vacuolar basic amino acid (VBA) transporter family of Saccharomyces cerevisiae, VBA4 encodes a vacuolar membrane protein with 14 putative transmembrane helices. Transport experiments with isolated vacuolar membrane vesicles and estimation of the amino acid contents in vacuoles showed that Vba4p is not likely involved in the transport of amino acids. We found that the vba4 Δ cells, as well as vba1 Δ and vba2 Δ cells, showed increased susceptibility to several drugs, particularly to azoles . Although disruption of the VBA4 gene did not affect the salt tolerance of the cells, vacuolar fragmentation observed under high salt conditions was less prominent in vba4 Δ cells than in wild type, vba1 Δ, and vba2 Δ cells. Vba4p differs from Vba1p and Vba2p as a vacuolar transporter but is important for the drug resistance and vacuolar morphology of S. cerevisiae . Graphical abstract: : Vba4p is a vacuolar membrane protein in the VBA transporter family of Saccharomyces cerevisiae (A). Disruption of VBA4 resulted in increased susceptibility to azoles (B).